Central and peripheral hemodynamic responses to orthostasis in hypertensive males with chronic venous disorders taking combined therapy with a calcium channel blocker and an angiotensin-converting enzyme inhibitor - S. V. Letyagina; V. M. Baev; T. Yu. Agafonova (Российский кардиологический журнал, 2020)
Aim. To study the characteristics of central and peripheral hemodynamic responses to orthostasis in hypertensive (HTN) males with chronic venous disorders (CVD) taking combined therapy with a calcium channel blocker (CCB) and an angiotensinconverting enzyme (ACE) inhibitor.Material and methods. In 46 men 30-50 years old with uncontrolled HTN taking antihypertensive therapy, a comparative assessment of the dynamics of systolic blood pressure (SBP), diastolic blood pressure (DBP), peripheral venous pressure (PVP), lumen diameter and area, blood flow velocity of superficial and deep veins of the left leg in response to orthostasis. Venous hemodynamics was studied by duplex ultrasound. PVP was assessed by oscillometry on the thigh and ultrasound of the great superficial vein. A comparative dynamic analysis of these parameters was carried out in patients of two groups: 23 hypertensive patients without CVD and 23 patients with HTN and CVD. CVD was assessed using Comprehensive Energy Assistance Program (CEAP). Orthostasis was performed before and after 14 days of antihypertensive therapy with a combination of CCB and ACE inhibitors.Results. Central and peripheral hemodynamic responses to orthostasis before treatment in patients of both groups was the same — a decrease in SBP, DBP and PVP, expansion of superficial and deep veins, and a decrease in venous blood flow velocity. As a result of treatment, 43 patients achieved the first target office SBP (<140 mm Hg). Of these, there were 21 HTN patients without CVD and 22 patients with CVD. After treatment, most responses to orthostasis in both groups was similar to pre-treatment ones. However, differences were also noted — in both groups, the DBP increased; SBP decreased only in men with CVD. In patients with CVD, the posterior tibial vein (PTV) dilated and blood flow velocity decreased after treatment in response to orthostasis, while in patients without CVD, there was a narrowing of PTV and blood flow acceleration. After treatment, patients with CVD were characterized by a larger diameter and area of the lumen of superficial and deep veins than those without CVD in response to orthostasis.Conclusion. Orthostasis before antihypertensive therapy in patients both with and without CVD is characterized by an identical hemodynamic response — a decrease in SBP, DBP, PVP expansion of superficial and deep veins, and a decrease in venous blood flow velocity. After 14-day antihypertensive therapy, there were differences in hemodynamic response between the study groups. In patients with HTN and CVD, CCB and ACE inhibitors therapy leads to a redistribution of central and peripheral circulation and increases the dilatation of the veins in response to orthostasis.